The whole lupus: Articulating biosocial interplay in systemic lupus erythematosus epidemiology and population disparities. (May 2018) - Kinsey, Dirk; Paul, Carolyn P.; Taylor, Denina; Caricchio, Roberto; Kulathinal, Rob J.; Hayes-Conroy, Allison
Abstract: Systemic lupus erythematosus (SLE), commonly known simply as lupus, is an autoimmune disease in which the body's immune system attacks healthy tissue and organs. Characteristic of the disease is a disproportionate effect on women and communities of color, both in terms of prevalence and severity of symptoms. Lupus is also both genetically driven and subject to external environmental conditions, many with place based corollaries. Thus, lupus presents a series of complex and intersecting biosocial questions regarding its origin and treatment, questions which transdisciplinary approaches are uniquely suited to address. In this paper, we propose a framework, incorporating critical approaches to the production of embodied formations of race and gender as well as new understandings of the impact of environmental conditions and lived experience at the genetic level, that can direct future research into lupus that is both more inclusive of a range of influences and more precise in its ability to treat and diagnose the disease. Highlights: Systemic lupus erythematosus (SLE) characterized by uneven prevalence and outcomes. SLE is the result of complex interactions between biological and social factors. Social categories may "become biological" in SLE disparities. A holistic model of SLE can provide richer data and lead to novel interventions.